Pengembangan Aplikasi Buku Penghubung Berbasis Web Sebagai Media Interaksi Sekolah – Orang Tua - Heri Kuswanto; Baiq Desi Dwi Arianti (Infotek: Jurnal Informatika dan Teknologi, 2022)
Communication book is one of supporting instrument of communication mechanism of teacher and parents considered not yet effective. Thus, it is necessary to develop a communication book in the digital environment as a solution to the problem. This study aims to develop communication book applications as a medium of communication between teachers and parents. This research uses research and development (R D) method with waterfall model approach that focused on efforts to produce a prototype of the product. Stages of research and development include communication, planning, modeling, construction, and deployment. Web-based development product using MVC design pattern concept with YII framework through the testing unit and ISO25010 standard quality. The result of this research and development is a prototype of communication book application as a proof of concept towards the approach used.